Can height categories replace weight categories in striking martial arts competitions? A pilot study - Dubnov-Raz, G.; Mashiach-Arazi, Y.; Nouriel, A.; Raz, R.; Constantini, N. W. (Journal of Human Kinetics, 2015)
In most combat sports and martial arts, athletes compete within weight categories. Disordered eating behaviors and intentional pre-competition rapid weight loss are commonly seen in this population, attributed to weight categorization. We examined if height categories can be used as an alternative to weight categories for competition, in order to protect the health of athletes.